Exploring the thermal degradation mechanisms of some polybenzoxazines under ballistic heating conditions in helium and air. (October 2018) - Thompson, Scott; Howlin, Brendan J.; Stone, Corinne A.; Hamerton, Ian
Abstract: The degradation behaviour of five polybenzoxazines (PBZs) is studied using pyrolysis-GC/MS. Upon heating to 800 °C in helium the PBZs generate a variety of similar pyrolysis products including aniline (the major product in all cases), substituted phenols, acridine, and 9-vinylcarbazole. During the initial stages of heating (200–300 °C) aniline is the dominant pyrolysis product; from 350 °C onwards substituted phenols are released, particularly 2-methylphenol and 2, 6-dimethyl phenol. The same major species are produced on heating in air, but in addition isocyanatobenzene is observed which results from the oxidation of Mannich bridges, along with a number of sulphurous species from the monomer containing a thioether bridge. This suggests that sulphur is more likely to be retained in the char in a helium atmosphere, but takes part in oxidative reactions to form pyrolysis fragments in air. During the ramped temperature cycles in both air and helium atmospheres the release of aniline was observed to rise, fall and then to rise again. This may be due a combination of the very high heating rate, poor thermal conduction of the polymer and the availability of the Mannich bridges to undergo breakdown. Highlights: Heated rapidly to 800 °C (helium) PBZs generate aniline, substituted phenols, acridine and 9-vinylcarbazole. Heated in air isocyanatobenzene is observed arising from oxidation of Mannich bridges. Sulphur retained in the char in helium atmosphere, but takes part in oxidative reactions to form pyrolysis fragments in air.